Pengaruh Literasi Keuangan, Sikap Keuangan, Paylater dan Media Sosial Terhadap Perilaku Pengelolaan Keuangan Mahasiswa Politeknik Negeri Padang - Roby Wirmansyah; Novrina Chandra; Muhammad Rafi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the influence of financial literacy, financial attitude, paylater usage, and social media on students’ financial management behavior. The research employed a quantitative approach using a questionnaire as the primary data collection instrument. The sampling technique applied in this study was non-probability sampling with a purposive sampling method. The research objects were students of Politeknik Negeri Padang, with sample criteria including active students who had previously used paylater services. A total of 404 responses were collected through the distributed questionnaires. The results of the study indicate that: (1) financial literacy does not have a significant effect on students’ financial behavior; (2) financial attitude has a significant effect on students’ financial behavior; (3) paylater usage significantly influences students’ financial behavior; and (4) social media significantly affects students’ financial behavior. The implications of this study suggest that financial knowledge alone is insufficient to shape good financial management behavior without being accompanied by consistent and disciplined financial habits. Students need to develop positive financial attitudes, such as self-control and budgeting discipline, to strengthen sound financial management. The use of paylater services should be exercised responsibly, limited to essential needs, and accompanied by timely repayment. Furthermore, social media should be utilized as a medium for financial education by engaging with beneficial content and avoiding content that encourages consumptive behavior.